Difference between midfield and forward football players in active and passive Body Mass Index as well as in the aerobic capacity - G Heta; L Bekolli; L Ramadani; Q Ramabaja; N Rashiti (Kazimierz Wielki University, 2020)
The importance of body construction for peak sportsis not fully defined as a precondition for achieving high results. Thepurpose of this paper is to determine the ratio of active and passive body mass index as well as maximum oxygen intake between midfield and forward football playersof the Kosovo Super League. To accomplish this goal, the research has included 50 midfielder players and 50 forward players of 10 teams of the Kosovo Super League. A total of six anthropometric variables, a motoric variable of aerobic type (the Cooper test) have been applied as well. For processing results, basic statistical and asymmetry parameters have been applied as well as the T-test analysis for independent groups. The research results show that there is a difference between midfield and forward football players in the ratio of active and passive body mass index and aerobic capacity and this difference is statistically significant p<0.05. The research shows that the morphologic and functional characteristics of footballers mainly depend on the role they have in the field.